Umbanda em Goiânia [manuscrito]: das origens ao movimento federativo (1948-2003) - NOGUEIRA, Leo Carrer (2009)
As a hybrid religion, Umbanda has elements of different sources in its daily practices. Thus, it doesn t have, necessarily, a single and centralized doctrine, in spite of several leaders had tried to impose a unified doctrine to it. That was one of the roles of several Umbanda Federations during the 20th century. Another role was to protect the shrines against the persecutions and repressions made by the State, Catholicism and the press. Therefore, the federations tried to protect the shrines and, on the other hand, they tried to control and centralize the religion, in its doctrines and socially. In the state of Goiás such control was held by the Umbanda and Candomblé Federation of Goiás, established in 1969 in Goiânia City. This dissertation, therefore, has as main objective to analyze the path of the religion in Goiânia, focusing its origins; the action of the Federation; as well as the conflicts and tensions created between it, the State repressive apparels and the shrines, from 1948 until 2003, when Goiânia was the scenario of a public repudiation of Umbanda, by some neo-Pentecostal churches against the exposition of seven sculptures depicting Orixás in a park of the city, which is known as Vaca-Brava Episode